HLA-C Genotyping Reveals Haplotype C*07 as a Potential Biomarker of Late Psoriasis Onset in Moroccan Patients - Chaimaa Benlabsir; Myriam Riyad; Imane El Idrissi Saik; Hanaa Ettayebi; Oussama Aazzane; Kawtar Nassar; Soukaina Zaher; Siham Bennani; Brahim Admou; Samy Housbane; Khalid Sadki; Soumiya Chiheb; et al. (Current Issues in Molecular Biology, 2023)
Psoriasis still has an unknown etiology. Genetic predisposition shows the association between HLA-Cw6 allele and psoriasis. Although biotherapies have been proven effective in psoriasis treatment, methotrexate (MTX) is still used as a first-line systemic therapy due to its efficacy/affordability, but the differential response to MTX is mostly related to interindividual genetic variability and remains an issue. Our study aimed to analyze HLA-C allele frequencies in a sample of Moroccan psoriatic patients and assess the therapeutic response to MTX. Whole blood of 54 Moroccan psoriatic patients was collected and DNA was extracted. Patients’ HLA-C locus was genotyped by PCR-SSO. Results were analyzed with Luminex xMAP Technology and Match-it DNA Evolution 3.4. HLA-C typing results of 77 sex- and age-matched unrelated non-psoriatic healthy subjects were included. We observed no difference in the allelic distribution of HLA-C between patients and healthy controls, suggesting that none of the HLA-C alleles were significantly associated with psoriasis. Moreover, the HLA-C*07 allele was associated with a late age at disease onset (>30 years old) (p = 0.007). No statistically significant association was found between HLA-C allele expression and response to MTX, despite a higher frequency of HLA-C*06 in responders compared to non-responders. Thus, HLA-C*07 could be a biomarker of late psoriasis onset in the Moroccan population.